2019
DOI: 10.1007/978-981-32-9755-5_14
|View full text |Cite
|
Sign up to set email alerts
|

Using Reverse Phase Protein Array (RPPA) to Identify and Target Adaptive Resistance

Abstract: Tumor cells and the tumor ecosystem rapidly evolve in response to therapy. This tumor evolution results in the rapid emergence of drug resistance that limits the magnitude and duration of response to therapy including chemotherapy, targeted therapy and immunotherapy. Thus, there is an urgent need to understand and interdict tumor evolution to improve patient benefit to therapy. Reverse phase protein arrays (RPPA) provides a powerful tool to evaluate and develop approaches to target the processes underlying one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…We also measured total and phosphoprotein levels in Bx1, Bx2, and Bx4 by RPPA (Figure 3E) and assessed pathway activity relative to the TCGA-BRCA cohort using proteomic pathway signatures. 12 We observed notable variations in pathways representing cell cycle regulation, hormone receptors, and PI3K-AKT signaling between biopsies (Figure 3D). For example, the “G0-G1”, “G2-M”, and “DNA Damage Checkpoint” pathways were increased in Bx1 relative to Bx2 and Bx4, as was phosphorylation of ATM, ATR, CDK1, and WEE1 (Figure 3E), suggesting that Bx1 had activated cell cycle checkpoints in response to DNA damage.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We also measured total and phosphoprotein levels in Bx1, Bx2, and Bx4 by RPPA (Figure 3E) and assessed pathway activity relative to the TCGA-BRCA cohort using proteomic pathway signatures. 12 We observed notable variations in pathways representing cell cycle regulation, hormone receptors, and PI3K-AKT signaling between biopsies (Figure 3D). For example, the “G0-G1”, “G2-M”, and “DNA Damage Checkpoint” pathways were increased in Bx1 relative to Bx2 and Bx4, as was phosphorylation of ATM, ATR, CDK1, and WEE1 (Figure 3E), suggesting that Bx1 had activated cell cycle checkpoints in response to DNA damage.…”
Section: Resultsmentioning
confidence: 93%
“…Figures S2E and S3A summarize the results of whole exome and Dual Index Degenerate Adaptor Sequencing (DIDA-Seq) of ctDNA from serial blood samples (Butler et al, 2019). Figure 3 also summarizes the results from RNA sequencing (RNAseq) to characterize the whole transcriptome ( Figure 3C), reverse phase protein arrays (RPPA) to profile the abundance of 450 proteins and phosphoproteins (Figures 3D, 3F;(Chen et al, 2019;Labrie et al, 2019a)), and a clinical multiplex protein analysis (Intracellular Signaling Protein Panel) of 22 cancer proteins and phosphoproteins ( Figure 3E; (Lee et al, 2018)). Computed pathway activity was estimated by assessing proteomic pathway signatures (Labrie et al, 2019a), total or phosphoprotein abundance levels, transcriptomic gene set variation analysis (GSVA; (Hanzelmann et al, 2013;Liberzon et al, 2015)), and transcriptional regulator networks (see Methods).…”
Section: An Integrated Clinical Omic and Multiscale Image Atlas Of mentioning
confidence: 99%
“…Inherent resistance, characterized by a pre-existing resistance to therapy, is difficult to predict in static biopsies that are acquired prior to therapy. We and other groups have demonstrated in multiple studies that the acquisition of a second biopsy early during the course of treatment is a powerful tool for analyzing how the tumor responds to therapy and for helping to identify mechanisms of adaptive resistance (reviewed in (Labrie et al, 2019a)). We have shown that serial samples can be collected pre and on-therapy with minimum risk to the patient and that these samples can be analyzed in “real time” using CLIA assays.…”
Section: Discussionmentioning
confidence: 99%
“…The RPPA were optimized to measure the levels of 300 proteins for downstream analysis. Normalized log2-transformed values of data were used throughout the reported analysis [14].…”
Section: Reverse-phase Protein Arraymentioning
confidence: 99%